IMPROVING STUDENTS SPEAKING SKILLS THROUGH RETELLING STORY BY USING PICTURE SERIES - Soraya M Nur; Ummi Khaerati Syam; Muh. Arief Muhsin, (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2021)
The objective of this research was to find out the significant of the improving the students’ speaking skill focus on speaking accuracy (pronunciation and vocabulary) and speaking fluency (effectiveness) by Using Story Telling with picture series strategy at the Second Year of SMA Muhammadiyah Limbung, Gowa. The researcher used Classroom Action Research (CAR). The researcher undertaken two cycles, for each cycle consisted of four meetings. Speaking test utilized as an instrument. The total subjects of the research were 31 students in class XI IIS 1. The real data was fetched by the researcher from the school to know the students’ speaking skill. The result of the students’ speaking test in cycle I and cycle II had significantly different score. There was a better improvement at the end of the action of the second cycle. The research findings demonstrated that by applying the method could improve students’ speaking skill and after evaluation in cycle I and cycle II, the mean scores improve from 6.3 in the first cycle to 7 in the second one which was categorized average. The students’ speaking skill was in a low level before the test in the first cycle and the position of the students’ speaking skill moved into a high level after the test in the second cycle. From these findings, the researcher deduced that by applying the strategy was one of effective and interesting speaking teaching strategy that could improve the students’ speaking skill in case of pronunciation, vocabulary, and effectiveness.